"Det är någonting som bara sitter kvar i kroppen" - en narrativ intervjustudie med barncanceröverlevare och deras partner - Andersson,Isabelle (2021)
This is a narrative study about being in a relationship with a child cancer survivor. Previous research in the field of partnership and cancer has focused on experiences of being a partner to a person who is currently in cancer treatment. There is a lack of knowledge regarding partnership to a person who has gone through a cancer treatment prior to being in the relationship. More children who are diagnosed with cancer survives today, which means that the group of adult child cancer survivors will only increase. With this growing group of adults finding their partner and getting into relationships it is important to look at how a relationship is affected by a child cancer treatment and experience. The empirical material consists of a total of 12 individual phone interviews with six couples where one of the two had been going through a cancer treatment as a child. The six couples who participated had been in a relationship for a various amount of time, ranging from a couple of months to 15 years. The narratives found in the interviews were divided into different types of narratives, problematizing and optimizing narratives. Narratives about complications from childhood cancer and conversations about the cancer experiences were two themes where the participants were divided into either problematizing or optimizing narratives. A third theme found in the interview were shared narratives, in this study meaning stories told by survivor and partner very similarly even though the interviews were conducted separately.
Keywords: partner; relationship; childhood cancer survivor; partnership; meaning making; narrative; barncanceröverlevare; barncancer